A Study on the Perceived Mobile Experience of Myeg Users - Hussain, Azham; Mkpojiogu, Emmanuel O.C.; Ishak, Norzila; Mokhtar, Nurhidayah (International Journal of Interactive Mobile Technologies (iJIM), 2019)
Mobility is the trend right now. It is transforming the user experience from the confines of the desk to the convenience of anytime-anywhere. MyEG Services Berhad ("MYEG") is a concessionaire for Malaysian Electronic-Government ("E-Government") MSC Flagship Application. MYEG builds, operates and owns the electronic channel that delivers services from various Government agencies to Malaysia citizens and businesses. To make their services up-to-date and in trend, MyEG app was developed and can also be used to check summons, pay summons, renew road-tax and renew auto insurance. To make sure that this application is efficient, fulfilling the customer needs and satisfaction, a usability evaluation was conducted. The evaluation was conducted in “Jabatan Teknologi Maklumat & Komunikasi, Politeknik Seberang Perai”, with 15 participants consisting of both lecturers and students. The think-aloud protocol was used while conducting the evaluation. The result of the evaluation revealed that overall the app is efficient, successful in fulfilling the users’ requirement and needs and promotes users mobile experience.